A humanized MDCK cell line for the efficient isolation and propagation of human influenza viruses - Takada, Kosuke; Kawakami, Chiharu; Fan, Shufang; Chiba, Shiho; Zhong, Gongxun; Gu, Chunyang; Shimizu, Kohei; Takasaki, Sara; Sakai-Tagawa, Yuko; Lopes, Tiago J. S.; Dutta, Jayeeta; Khan, Zenab; et al. (Nature microbiology, 2019)
Here, we developed hCK, a Madin-Darby canine kidney (MDCK) cell line that expresses high levels of human influenza virus receptors and low levels of avian virus receptors. hCK cells supported human A/H3N2 influenza virus isolation and growth much more effectively than conventional MDCK or human virus receptor-overexpressing (AX4) cells. A/H3N2 viruses propagated in hCK cells also maintained higher genetic stability than those propagated in MDCK and AX4 cells. The authors report the development of a Madin-Darby canine kidney (MDCK) cell line that is more suitable than conventional MDCK or human virus receptor-overexpressing cells for the isolation and propagation of human influenza viruses without cell culture-adaptive mutations.